Safe commutation studies for single phase matrix converter operation as inverter / Siti Zaliha Mohammad Noor and Mustafar Kamal Hamzah - Mohammad Noor, Siti Zaliha; Hamzah, Mustafar Kamal (Research Management Institute (RMI), 2010)
Electric power is the muscle of the modern industry and power electronics make its utilization smarter. The objective of power electronics is to improve the quality and utilization of electric power. Power Electronics have revolutionized the concept of power control for power converters and for control of electric motor drives. They are based primarily on the switching of power semiconductor devices. Converter systems comprised switches, reactive component such as inductance, capacitance and transformers. They may be classified into four basic form of power conversion that includes; a) AC to DC Conversion, b) AC to AC Conversion, c) DC to AC Conversion and d) DC to DC Conversion. There are cases where it is convenient to generally define these converters in terms of its four quadrant operation…